Предмет: Математика,
автор: sugaksu0528
упростите выражение (3x-4)(5x+2)-3(2x-3)²
Ответы
Автор ответа:
4
15х в квадрате +6х - 20х -8 + 4х в квадрате - 6х-6х+ 9= 19х в квадрате - 26х + 1;
Автор ответа:
6
=15х^2+6х-20х-8-3(4х^2-12х+9)=
=15х^2-14х-8-12х^2+36х-27=3х^2+22х-35
=15х^2-14х-8-12х^2+36х-27=3х^2+22х-35
Похожие вопросы
Предмет: Українська мова,
автор: esipovichdasha
Предмет: Окружающий мир,
автор: sdkhgfioh
Предмет: Русский язык,
автор: Eleonora20061
Предмет: Алгебра,
автор: Pavoka
Предмет: Алгебра,
автор: nickpuzanoff2018